VIRTUAL LEARNING ENVIRONMENT WITH REFERENCE TO THE PERCEIVED PREPAREDNESS OF COLLEGE STUDENTS IN MADURAI DISTRICT: A STUDY - Jeyanthi, R. Murugananda; S., Aravind (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines college student’s readiness for a newly introduced virtual learning environment by analyzing factors influencing their skills and attitudes towards web-based courses. Grounded in the technology acceptance model, the research explores user acceptance and behavior among students in Madurai district, known for their regular internet and computer usage. Focusing on moderate to heavy technology users, the study aims to illuminate their readiness and willingness to adopt virtual learning platforms. Key findings indicate widespread engagement of undergraduate students with virtual learning environments, particularly through platforms like the National Digital Library of India (NDL) and Study Webs of Active-learning for Young Aspiring Minds (SWAYAM). Email emerges as the predominant internet activity, crucial for student communication. Moreover, a significant number of students demonstrate awareness and active use of NDL and other open education resources, underscoring their seamless integration into academic routines.